Space Politics and Policies: Chinese-Javanese Ethnic Segregation in Parakan and Integration Effort - Sodiq, Ibnu; Santoso, Eko (Paramita: Historical Studies Journal, 2022)
This study aims to describe the history of the dynamic relationship between Chinese and Javanese in Parakan, Temanggung Regency, Central Java. The method used is the historical research method which consists of four stages. These are heuristics, source criticism, interpretation and historiography. The study used qualitative analysis with a phenomenological approach. The ethnic Chinese-Javanese relationship in Parakan had ups and downs, especially during the colonial period until after the G30S incident. As a minority group, the Chinese were often racially discriminated against. Discrimination and negative sentiment are also driven by the inequality of socio-economic conditions between Chinese-Javanese. Moreover, the state, through various regulations, has contributed to strengthening this segregation, in the form of space politics and policies. That is, Parakan City is divided into two sub-districts, Parakan Kulon (Kauman) and Parakan Wetan (Chinatown). The colonial government also contributed to the existence of a different socio-economic stratification, prioritizing the ethnic Chinese as a higher stratum. This construction was preserved until the New Order era. These differences created disharmonious relationship, often ending in conflict. Moreover, the exclusive and elitist attitude were held by most of the ethnic Chinese. Some of these things eventually become the inhibiting factors for the integration process of perfect segregation. In the end, the eternal Javanese sentiment with the Chinese ethnicity hindered the process of recognizing the same national identity. Even there is an integration effort.Penelitian ini bertujuan mengurai sejarah dinamika hubungan etnis Tionghoa dengan masyarakat Jawa di Parakan, Kabupaten Temanggung, Jawa Tengah. Metode yang digunakan ialah metode penelitian sejarah yang terdiri dari empat tahapan. Yakni heuristik, kritik sumber, interpretasi dan historiografi. Penelitian ini menggunakan analisis kualitatif dengan pendekatan fenomenologi. Hubungan etnis Tionghoa-Jawa di Parakan mengalami pasang surut dari masa ke masa, terutama periode kolonial hingga pasca peristiwa G 30 S. Sebagai kelompok minoritas, etnis Tionghoa acapkali mengalami diskriminasi rasial. Diskriminasi dan sentimen negatif juga didorong adanya ketimpangan kondisi sosial-ekonomi antara Thionghoa-Jawa. Terlebih negara, melalui berbagai regulasi turut mengokohkan segregasi tersebut dalam bentuk politik ruang dan kebijakan. Bentuknya, Kota Parakan dibagi menjadi dua wilayah yaitu kelurahan Parakan Kulon (Kauman) dan Parakan Wetan (Pecinan). Pemerintah colonial juga turut membidani lahirnya stratifikasi social-ekonomi yang berbeda di antara keduanya, dengan memprioritas etnis Tionghoa sebagai strata yang lebih tinggi. Konstruksi yang demikian ini dikekalkan hingga masa pemerintahan orde baru. Berbagai perbedaan ini yang membuat ketidakharmonisan hubungan keduanya seringkali memuncak dalam bentuk konflik. Terlebih, adanya sikap eksklusif dan elitis yang dipegang sebagian besar etnis Tionghoa. Beberapa hal ini akhirnya menjadi faktor penghambat proses integrasi atas segregasi yang kadung mapan. Pada akhirnya sentimen Jawa terhadap etnis Tionghoa yang lestari menghambat proses pengakuan atas identitas kebangsaan yang sama. Sekalipun upaya pengintegrasiaan itu ada. Cite this article: Sodiq, I. Santoso, E. (2022). Space Politics and Policies: Chinese-Javanese Ethnic Segregation in Parakan and Integration Effort Paramita: Historical Studies Journal, 32(1), 78-85. http://dx.doi.org/10.15294/paramita.v32i1.31389